2011
DOI: 10.1074/jbc.m111.234161
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis Reveals a Novel Nuclear Factor-κB (NF-κB)-binding Site in Alu-repetitive Elements

Abstract: Background:The transcription factor NF-B is a critical regulator of immune response pathways. Results: 11% of total NF-B binding events in humans occur at the Alu-B element present in Alu repeats. Conclusion: NF-B has a primate-specific function and a role in human evolution. Significance: Repetitive elements expand the repertoire of binding sites to engage new genes into regulatory networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 48 publications
2
54
0
Order By: Relevance
“…Gene Expression Analysis DNA microarray analyses were performed as previously described (Antonaki et al, 2011) with three biological replicates on Affymetrix HG133plus2.0 chips. FC R 1.5 and p < 0.05 were used for DE calling, except for shmH2A1, where FC R 1.3 and p < 0.1 were used to detect more subtle changes.…”
Section: Chip-seqmentioning
confidence: 99%
“…Gene Expression Analysis DNA microarray analyses were performed as previously described (Antonaki et al, 2011) with three biological replicates on Affymetrix HG133plus2.0 chips. FC R 1.5 and p < 0.05 were used for DE calling, except for shmH2A1, where FC R 1.3 and p < 0.1 were used to detect more subtle changes.…”
Section: Chip-seqmentioning
confidence: 99%
“…There is ample evidence that Alu transposition, recombination, and expansion have contributed to genome evolution and changes to gene regulation (11,12). Alu repeats contain motifs recognized by several transcription factors (TFs) including SP1, p53, c-MYC, ANRIL, NF-κB (13), and previous work has suggested that they can function as enhancers (14). …”
Section: Introductionmentioning
confidence: 99%
“…Yet, the repertoire of active cis-elements per cell type is not constant, and introduction of a new transcription factor (TF) upon signaling also activates hitherto inactive enhancers (Kaikkonen et al 2013;Ostuni et al 2013;Brown et al 2014). Notably, high-throughput studies of the binding preferences of various NF-κB dimers in vitro (Wong et al 2011;Siggers et al 2012) and in vivo (Antonaki et al 2011;Zhao et al 2014) showed that binding to nonconsensus motifs is permissible. Still, how binding to noncanonical sites underlies the different NF-κB functions remains unknown.…”
mentioning
confidence: 99%